Tc-99m-sestamibi scintigraphy used to evaluate tumor response to neoadjuvant chemotherapy in locally advanced breast cancer: A quantitative analysis - Koga, Katia Hiromoto [UNESP]; Moriguchi, Sônia Marta [UNESP]; Nahas Neto, Jorge [UNESP]; Peres, Stela Verzinhasse; Da Silva, Eduardo Tinois [UNESP]; Sarri, Almir Jose; Michelin, Odair Carlito [UNESP]; Marques, Mariângela Esther Alencar [UNESP]; Griva, Beatriz Lotufo [UNESP] (Spandidos Publ Ltd, 2010)
To evaluate the tumor response to neoadjuvant chemotherapy, Tc-99m-sestamibi breast scintigraphy was proposed as a quantitative method Fifty-five patients with ductal carcinoma were studied They underwent breast scintigraphy before and after neoadjuvant chemotherapy, along with clinical assessment and surgical specimen analysis The regions of interest on the lesion and contralateral breast were identified, and the pixel counts were used to evaluate lesion uptake in relation to background radiation The ratio of these counts before to after neoadjuvant chemotherapy was assessed The decrease in uptake rate due to chemotherapy characterized the scintigraphy tumor response The Kruskal-Wallis test was used to compare the mean scintigraphic tumor response and histological type Dunn's multiple comparison test was used to detect differences between histological types The Mann-Whitney test was used to compare means between quantitative and qualitative variables scintigraphic tumor response vs clinical response and uptake before chemotherapy vs scintigraphic tumor response The Spearman's test was used to correlate the quantitative variables of clinical reduction in tumor size and scintigraphic tumor response All of the variables compared presented significant differences The change in Tc-99m-sestamibi uptake noted on breast scintigraphy, before to after neoadjuvant chemotherapy, may be used as an effective method for evaluating the response to neoadjuvant chemotherapy, since this quantification reflects the biological behavior of the tumor towards the chemotherapy regimen Furthermore, additional analysis on the uptake rate before chemotherapy may accurately predict treatment response
Keywords: breast cancer; neoadjuvant chemotherapy; Tc-99m-sestamibi; scintigraphy; quantitative analysis